Validation Study of Image-Based Fractional Flow Reserve During Coronary Angiography. (September 2017) - Pellicano, Mariano; Lavi, Ifat; De Bruyne, Bernard; Vaknin-Assa, Hana; Assali, Abid; Valtzer, Orna; Lotringer, Yonit; Weisz, Giora; Almagor, Yaron; Xaplanteris, Panagiotis; Kirtane, Ajay J.; Codner, Pablo; et al.
Abstract : Background—: Fractional flow reserve (FFR), an index of the hemodynamic severity of coronary stenoses, is derived from invasive measurements and requires a pressure-monitoring guidewire and hyperemic stimulus. Angiography-derived FFR measurements (FFRangio ) may have several advantages. The aim of this study is to assess the diagnostic performance and interobserver reproducibility of FFRangio in patients with stable coronary artery disease. Methods and Results—: FFRangio is a computational method based on rapid flow analysis for the assessment of FFR. FFRangio uses the patient's hemodynamic data and routine angiograms to generate a complete 3-dimensional coronary tree with color-coded FFR values at any epicardial location. Hyperemic flow ratio is derived from an automatic resistance-based lumped model of the entire coronary tree. A total of 203 lesions were analyzed in 184 patients from 4 centers. Values derived using FFRangio ranged from 0.5 to 0.97 (median 0.85) and correlated closely (Spearman ρ=0.90; P <0.001) with the invasive FFR measurements, which ranged from 0.5 to 1 (median 0.84). In Bland–Altman analyses, the 95% limits of agreement between these methods ranged from −0.096 to 0.112. Using an FFR cutoff value of 0.80, the sensitivity, specificity, and diagnostic accuracy of FFRangio were 88%, 95%, and 93%, respectively. The intraclass coefficient between 2 blinded operators was 0.962 with a 95% confidence interval from 0.950 to 0.971, P <0.001. Conclusions—: There is a high concordance between FFRangio and invasive FFR. The color-coded display of FFR values during coronary angiography facilitates the integration of physiology and anatomy for decision making on revascularization in patients with stable coronary artery disease. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT03005028. Abstract : Supplemental Digital Content is available in the text.